Times Square red, Times Square blue - Delany, Samuel R. (Sexual cultures., 2019)
Twentieth anniversary edition of a landmark book that cataloged a vibrant but disappearing neighborhood in New York City. In the two decades that preceded the original publication of Times Square Red, Times Square Blue, Forty-second Street, then the most infamous street in America, was being remade into a sanitized tourist haven. In the forced disappearance of porn theaters, peep shows, and street hustlers to make room for a Disney store, a children's theater, and large, neon-lit cafes, Samuel R. Delany saw a disappearance, not only of the old Times Square, but of the complex social relationships that developed there. Samuel R. Delany bore witness to the dismantling of the institutions that promoted points of contact between people of different classes and races in a public space, and in this hybrid text, argues for the necessity of public restrooms and tree-filled parks to a city's physical and psychological landscape. This twentieth anniversary edition includes a new foreword by Robert Reid-Pharr that traces the importance and continued resonances of Samuel R. Delany's groundbreaking Times Square Red, Times Square Blue.